A Synergistic Transcriptional Regulation of Olfactory Genes Drives Blood-Feeding Associated Complex Behavioral Responses in the Mosquito Anopheles culicifacies - Das De, Tanwee; Thomas, Tina; Verma, Sonia; Singla, Deepak; Chauhan, Charu; Srivastava, Vartika; Sharma, Punita; Kumari, Seena; Tevatiya, Sanjay; Rani, Jyoti; Hasija, Yasha; Pandey, Kailash C.; et al. (Frontiers in Physiology, 2018)
Decoding the molecular basis of host seeking and blood feeding behavioral evolution/adaptation in the adult female mosquitoes may provide an opportunity to design new molecular strategy to disrupt human-mosquito interactions. Although there is a great progress in the field of mosquito olfaction and chemo-detection, little is known about the sex-specific evolution of the specialized olfactory system of adult female mosquitoes that enables them to drive and manage the complex blood-feeding associated behavioral responses. A comprehensive RNA-Seq analysis of prior and post blood meal olfactory system of An. culicifacies mosquito revealed a minor but unique change in the nature and regulation of key olfactory genes that may play a pivotal role in managing diverse behavioral responses. Based on age-dependent transcriptional profiling, we further demonstrated that adult female mosquito’s chemosensory system gradually learned and matured to drive the host-seeking and blood feeding behavior at the age of 5-6 days. A time scale expression analysis of Odorant Binding Proteins (OBPs) unravels unique association with a late evening to midnight peak biting time. Blood meal-induced switching of unique sets of OBP genes and Odorant Receptors (ORs) expression coincides with the change in the innate physiological status of the mosquitoes. Blood meal follows up experiments further provide enough evidence that how a synergistic and concurrent action of OBPs-ORs may drive ‘prior and post blood meal’ associated complex behavioral events. A dominant expression of two sensory appendages proteins (SAP-1 & SAP2) in the legs of An. culicifacies suggests that this mosquito species may draw an extra advantage of having more sensitive appendages than An. stephensi, an urban malarial vector in the Indian subcontinents. Finally, our molecular modeling analysis predicts crucial amino acid residues for future functional characterization of the sensory appendages proteins which may play a central role in the regulating multiple behaviors of An. culicifacies mosquito.